Ultrahigh-Performance Fiber-Supported Iron-Based Ionic Liquid for Synthesizing 3,4-Dihydropyrimidin-2-(1 H )-ones in a Cleaner Manner - Zhang, Tian; Shi, Xian-Lei; Hu, Qianqian; Gong, Honghui; Shi, Keren; Li, Zhenhua (Langmuir, 2024)
Herein, a fiber-supported iron-based ionic liquid as a type of fibrous catalyst has been developed for the synthesis of bioactive 3,4-dihydropyrimidin-2-(1 )-ones (DHPMs) via three-component Biginelli reactions in a cleaner manner. The described fibrous catalyst was obtained from the commercially available polyetheretherketone (PEEK) fiber by postfunctionalization processes and was characterized and analyzed in detail by means of diversified technologies. Furthermore, the fiber-supported iron-based ionic liquids could mediate the classical three-component Biginelli reactions to proceed smoothly to gain a variety of substituted DHPMs with yields of up to 99%. The superior catalytic activities of the fibrous catalyst were ascribed to the quasi-homogeneous medium by ionic liquids generated in the surface layer of the PEEK fiber, which could afford an appropriate reaction zone and could further be available for the aggregation of substrates to facilitate the three-component reaction. Notably, the fibrous catalyst is available for recycling over 10 runs just by a pair of tweezers, and the operational procedure was capable of enlarging the catalytic system to the gram-scale without any performance degradation, which provided a cleaner manner to take advantage of the iron-based catalyst in organic synthesis with potential industrialization prospects.